Energy Cohesive Calculation for Some Pure Metals Using the Lennard-Jones Potential in Lammps Molecular Dynamics. (March 2020) - Mardiyah, R U; Arkundato, A; Misto; Purwandari, E
Abstract: It has been determined by molecular dynamics simulation method the parameter potentials ( ε, σ ) of the Lennard-Jones potential based on the cohesive energy value for some pure metals. The LAMMPS molecular dynamics software was used to simulate and calculate the cohesive energy of the metals. To determine the best value of ( ε, σ ) we verified all calculations using the available experimental data of cohesive energy of the metals. The discrepancy of cohesive energy between simulation and experimental data were limited not more than 0.1 % to get best value of the Lennard-Jones parameter potentials ( ε, σ ).